The level of political participation among youth of Brgy. Sulangan, Guiuan, E. Samar. - Abayon, Joenard (Joenard Abayon [and] Riza Baldizar Odullo, 2010)
Barangay Sulangan is one of the barangay of Guiuan, Eastern Samar. Since the manner in which citizens participate in their political process is integral to the manner in which the system functions, the question of how and why persons become involved in politics is germane to the concerns of every man. Hence, it is for this reasons that the researchers become interested in studying the level of political participation among the youth. This study aims to determine the level of political participation the youth have and how it is affected by their socio-economic and demographic factors.